Keanekaragaman Hayati Flora Habitat Bekantan pada Kawasan Ekowisata, Kabupaten Tapin, Kalimantan Selatan - Anggi Pangestu; Yadi Setiadi; Hadi Susilo Arifin (Institut Pertanian Bogor, 2019)
Land use changes from Malaleuca cajuputi swamp forest ecosystem to agriculture production area and settlement land decrease habitat of proboscis monkeys. The habitat position at the edge of the river and high accessibility caused faster habitat damage. In addition, forest fires occurred in 2015 has caused significant losses of flora and fauna biodiversity in the area. In order to know the type of plants in the study site, the vegetation analysis was conducted. The study site consisted of 19 species of lower plant and 4 types of trees. Dominant species and codominant of study site are widely distributed, indicating the existence of competition in obtaining nutrients and space. At the under storey plant level was dominated by Stenochlaena palustris and Scirpus grossus at the locations A and B whereas at location C was dominated by the Eleocharis dulcis and Jussieua erecta. In the types of trees, the dominant trees were Melaleuca cajuputi, Muntingia sp, Alstonia angustifolia, Shorea balangeran, and Albizia falcataria. In all three locations, there were low similarity values in the plant species below, the level of seedlings, and samplings.